Imaji Biblis dan Dogmatis tentang Pertobatan yang Menggembirakan - Aloysius Wahyu Endro Suseno (P3TK, Sanata Dharma University, 2017)
Repentance is one of the most important theme in Gods salvific plan for human being. Somehow nowadays, repentance seems unfavourable for many. People tend to look down on guilty feeling, avoiding any form of judgement or punishment, and to fall into misunderstandings of repentance as well as the sacrament of reconciliation. Repentance needs to be preached continuously, yet with a more positive approach. One way to do it is to use a joyful image of repentance, which indeed can be found in the Scripture and the Doctrine of Church. By finding those images, repentance will bring more joy, not only for the angels in heaven (cf. Luke 15:10), but for the people in the world, especially those who has good will to repent.